Critical reappraisal of the skeletal anatomy of aptian pipoid frogs from the crato formation, north-central brazil, the earliest known pipimorphs of South America - Baez, Ana Maria (2019)
The clade Pipoidea comprises the peculiar monotypic fossorial Rhinophrynus and the also peculiar and highly aquatic Pipidae. Various fossil taxa have been described as stem-group Pipidae, the clade encompassing the most recent ancestor of living pipids and all of its descendants, distributed today in the former Western-Gondwanan Africa and South America. In this regard, the name Pipimorpha was coined for crown-group Pipidae and all pipoid taxa more closely related to it than to Rhinophrynidae. Although pipimorphs possibly diverged from stem rhinophrynids in the Late Jurassic, the oldest known representatives in South America are from the Aptian Crato Formation, Ceará State. Pipimorphs had been considered to be possibly present in that unit based on a poorly preserved specimen (MPSC-An 892) with synapomorphies of this group (e.g., long metapodials). Recently, a single articulated specimen in dorsal aspect from these beds formed the basis of a new pipimorph genus, Cratopipa. Re-examination of this specimen (UFRJ-DG 05 A) allowed us to clarify the identity of bones (e.g., pterygoid, squamosal, exoccipitals, angulosplenial, cleithrum, scapula) and of traits, including putative diagnostic features, that had been misinterpreted. This information led to an amended diagnosis and new restoration, as well as to the revision of the scoring of characters for phylogenetic analysis (19 characters out of 165 were scored differently from the original study and 16 whose state was previously considered unknown). Despite disparate preservation, available information suggests that those two specimens represent different pipimorph taxa based on features such as the different proportions of hindlimb segments